2019
DOI: 10.1371/journal.pone.0223823
|View full text |Cite
|
Sign up to set email alerts
|

Post-overdose interventions triggered by calling 911: Centering the perspectives of people who use drugs (PWUDs)

Abstract: BackgroundOpioid overdose deaths have increased exponentially in the United States. Bystander response to opioid overdose ideally involves administering naloxone, providing rescue breathing, and calling 911 to summon emergency medical assistance. Recently in the US, public health and public safety agencies have begun seeking to use 911 calls as a method to identify and deliver post-overdose interventions to opioid overdose patients. Little is known about the opinions of PWUDs about the barriers, benefits, or p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 30 publications
1
48
0
Order By: Relevance
“…Participants cited 4 main barriers that may impede rates of naloxone acceptance, possession, and use: (1) stigma related to substance use, (2) indifference toward overdose, (3) fear of the negative consequences of carrying naloxone, and (4) fear of misrecognizing the need for naloxone. Some of these barriers have been identified by other researchers, including the fear of precipitating withdrawal sickness, stigma, and the fear of arrest [ 12 , 24 , 36 , 37 ]. Our study participants cited stigma toward drug users and concerns of being outed as a drug user as influencing naloxone-related practices, including decisions about whether or not to carry or prominently display naloxone when carrying it.…”
Section: Discussionmentioning
confidence: 99%
“…Participants cited 4 main barriers that may impede rates of naloxone acceptance, possession, and use: (1) stigma related to substance use, (2) indifference toward overdose, (3) fear of the negative consequences of carrying naloxone, and (4) fear of misrecognizing the need for naloxone. Some of these barriers have been identified by other researchers, including the fear of precipitating withdrawal sickness, stigma, and the fear of arrest [ 12 , 24 , 36 , 37 ]. Our study participants cited stigma toward drug users and concerns of being outed as a drug user as influencing naloxone-related practices, including decisions about whether or not to carry or prominently display naloxone when carrying it.…”
Section: Discussionmentioning
confidence: 99%
“…This finding is important as many of our participants' healthcare interactions began with a call to EMS, to which law enforcement was often the first responder. Wagner et al ( 2019 ) similarly found that people in urban areas who use drugs equated a 911 call for a medical reason to calling the police. Our study found that this sentiment may be exacerbated in rural settings where our participants were often well-known to a small police force and, not uncommonly, had ties to some officers through shared school histories, neighborhoods or family relations.…”
Section: Discussionmentioning
confidence: 99%
“…Further work is needed to explore whether African-American participants are less likely to access or use naloxone and if so, the mechanisms explaining decreased access and use. High rates of incarceration among African-Americans in Baltimore City [38] and nationally [39] (although low among this sample at this point in time) may lead to fear of police involvement and incarceration from carrying or giving naloxone and from calling 911 among African American PWID [35,40].…”
Section: Discussionmentioning
confidence: 99%